The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2014
DOI: 10.1016/j.jsams.2014.11.362
|View full text |Cite
|
Sign up to set email alerts
|

Total and domain-specific sitting time among employees in desk-based work settings in Australia

Abstract: Objective: To describe the total and domain-specific daily sitting time among a sample of Australian office-based employees. Methods:In April 2010, paper-based surveys were provided to desk-based employees (n=801) in Victoria, Australia. Total daily and domain-specific (work, leisure-time and transport-related) sitting time (minutes/day) were assessed by validated questionnaires. Differences in sitting time were examined across socio-demographic (age, sex, occupational status) and lifestyle characteristics (ph… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
3
0

Year Published

2016
2016
2016
2016

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(5 citation statements)
references
References 12 publications
2
3
0
Order By: Relevance
“…In our full model, age was observed to be negatively associated with sedentary time at work, which corroborates many previous studies (26,30,32). BMI also tended to be negatively associated with time spent sedentary, and this contradicts previous studies (26,29).…”
Section: Gupta Et Alsupporting
confidence: 76%
See 3 more Smart Citations
“…In our full model, age was observed to be negatively associated with sedentary time at work, which corroborates many previous studies (26,30,32). BMI also tended to be negatively associated with time spent sedentary, and this contradicts previous studies (26,29).…”
Section: Gupta Et Alsupporting
confidence: 76%
“…The performance of the full model based on age, job group, BMI, and self-reported OST and OPA was similar to the best performances of previous questionnaires on occupational sedentary and physical activity (45)(46)(47). The performance of our model was even better than previously developed models using a customized set of variables to predict self-reported OST or OPA (26,29,30). Also, these previous models produce estimates of self-reported OST or OPA, and thus do not adjust for the bias present in these self-reports, relative to objectively measured data.…”
Section: Gupta Et Alsupporting
confidence: 73%
See 2 more Smart Citations
“…Hence, physical inactivity represents sedentary behavior that does not involve muscle contraction, which is most prevalent during sitting and lying. Recent studies revealed that accelerometermeasured mean daily sedentary time was 8.2 hrs/day among New York City adults [13], whereas Australian desk workers reported an average of 9.0 hrs/day of sitting time [14]. Physical inactivity is not restricted to the general population; it can be observed in (half-)marathon runners as they have reported sitting 10.75 hrs/day on workdays and 8 hrs/day on non-workdays [15].…”
Section: Physical Inactivity and Sitting Behaviormentioning
confidence: 99%